Development of a Suicide Prevention Surveillance Model in Patients with Depression at Krasaesin Hospital - Chaisawat, Nanvalai (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Suicide is a significant public health issue, particularly among patients with depression who are at high risk. Therefore, developing a model for suicide prevention surveillance that is appropriate for the service unit context is necessary. This study aimed to examine the situation and factors affecting suicide, develop a model for suicide prevention surveillance, and evaluate the model's effectiveness in patients with depression at Krasaesin Hospital. Methods The research and development process was divided into three steps: 1) Study the situation and factors affecting suicide and a suicide prevention surveillance model through in-depth interviews with 14 patients aged 15 years and older with a history of suicide attempts and focus group discussions with 10 mental health service providers, including doctors, pharmacists, psychiatric nurses, home visit nurses, psychologists, and primary care psychiatric nurses from five facilities; 2) Develop a model for suicide prevention surveillance based on qualitative data analysis; 3) Test and evaluate the effectiveness of the model in 34 patients with depression, collecting pre- and post-test data using the 9Q Depression Screening Questionnaire, the 8Q Suicide Risk Assessment, and the Suicide Prevention Behavior Questionnaire. Data were analyzed using the paired sample t-test, and the benefits and value of the model were assessed. Results Research findings indicated that the screening and assessment of suicide risk still lack a systematic approach. The influencing factors included personal factors, experiences, health, and environment. The model assisted in developing staff capabilities, screening at-risk groups, promoting family and community networks, managing mental health data, providing individual care, following up to prevent recurrence, and utilizing technology. After implementing the model, depression levels decreased from 2.68 ± 0.72 to 0.52 ± 0.83, suicide risk decreased from 1.59 ± 0.65 to 0.38 ± 0.49, and suicide prevention behaviors increased from 77.32 ± 7.17 to 86.21 ± 4.98, with statistical significance (p < .001). The model was beneficial for systematic surveillance and enhancing confidence in caring for patients with depression. Conclusion and Recommendations The model is suitable for the context of community hospitals. It is effective in reducing depression and suicide risk and increasing preventive behaviors. It helps develop staff potential, monitor individual patients, and promote participation. The model should be implemented in the development of health service systems and communities.